The National Strategy on Financial Literacy: A Conceptual Review of South African Perspectives - Ifeanyi, Mbukanma; Rena, Ravinder; Prinsloo, J.J. Hein (Journal of Reviews on Global Economics, 2019)
The relevance of financial literacy in the lives of individuals has attracted several stakeholders from different parts of the world in the quest to provide the required financial knowledge for households to manage their financial wellbeing. Accordingly, previous studies show that financial literacy serves as a mechanism to enhance the ability of households to better allocate financial resources with regard to savings and wealth creation over their lifetimes in a world of uncertainty and imperfect insurance. Thus, this study provides a literature review on global initiatives, strategies and programmes on financial literacy as well the perspectives of financial literacy programmes in South Africa. As such, it is the objective of this study to ascertain from previous literatures the factors that hinders the smooth delivery of financial literacy programmes in South Africa. Thus, the researcher employed a descriptive literature review method to achieve this objective. The findings of this study identifies that there is a growing need for a continuous financial literacy campaign especially in South Africa as the aging populations are confronted with intensified pressure on standardised plan for future financial well-being. However, the challenges of financial literacy programmes in South Africa was ascertained which forms part of the factors that hinders smooth campaign of financial literacy programmes in South Africa. Hence, this study recommends practical intervention factors of financial literacy programme in South Africa, which is expected to assist policy makers in formulating the right financial knowledge delivery programmes in South Africa.